Martha Inc : the incredible story of Martha Stewart Living Omnimedia - Byron, Christopher (New York, NY Wiley, 2002)
Investigates Martha Stewart's empire to uncover evidence that her difficult childhood and years on Wall Street contributed to her later stellar success in the magazine business
Literary Guild, 7/04
Keywords: Stewart, Martha; Martha Stewart Living Omnimedia; Artisans--United States--Biography; Businesswomen--United States--Biography